Methods of Dogmatic Discourse in the Dispute over the Immaculate Conception of the Blessed Virgin Mary as Exemplified by German Dominican Theologians from the 13th to the 16th Century - Ferdek, Bogdan (Verbum Vitae, 2024)
The important problem of the publication is expressed by two questions: what method was used by German Dominican theologians who were supporters of the Immaculate Conception? How did the change in method change the view of the Immaculate Conception? The path to solving the problem has three stages. The first of them is a reconstruction of the views on the Immaculate Conception of German Dominican theologians. The next stage examines these views in terms of the method used. The final stage is a critical look at the methods used by Dominican supporters of the Immaculate Conception. The method used in the article consists of: systematization of the views of German Dominicans, analysis of the methods used by them and a discourse on the methods of the supporters of the Immaculate Conception with the opponent of this opinion, St. Thomas Aquinas. The change of method, from the scholastic method to the liturgical method (lex orandi – lex credendi), the argument from congruity (ex convenientia), and typological exegesis, has led a few Dominican theologians to the opinion that Mary was preserved or purified from original sin, or that she was conceived without original sin. The methods used by Dominican supporters of the Immaculate Conception have weaknesses. They resemble a circumstantial trial, which provides a high degree of probability, but not proof. This weakness of the methods is exposed by the discourse of these methods with the scholastic method of St. Thomas. This discourse results in the postulate of reinterpreting the Immaculate Conception. We should return to the biblical term “sanctification” and explain that Mary was saved by a more sublime sanctification. This would prevent the immaculate conception of Jesus from being equated with the immaculate conception of Mary. Only Jesus is Immaculate because He was conceived by the Holy Spirit, and His Mother, conceived by Joachim and Anna, was saved by a more sublime sanctification.